ANALISIS DAYA TAMPUNG KAMPUNG WISATA KELEMBAK - Edy Wibowo, Agung; Sianipar, Baktivillo (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2022)
This study intends to provide an initial description of a site plan of development project which to develop into a tourist attraction. Ecotourism activities have now become an integral part of tourism which oriented towards ecotourism, one of the ecotourism that is currently booming and is becoming a leading tourism in coastal areas is Mangrove forest tourism. Kelembak Village as part of the Nongsa District, located in the Riau Archipelago Province, has an area of ​​6 hectares. This spacious area has a natural beauty that has the potential to become a tourist location. This study also provides an overview of the calculation above the RCC value is 149,95 or 150 tourists per day, so the estimated number of tourists that the area can take in one month is 149,95 times 30 days equal to 4.498,5 tourists or visitors. When compared with the current number of visits, the capacity of the Kelembak Village tourist site can still provide a comfortable space for tourists with the risk of a tendency to damage biological habitats that can still be controlled and monitored. The results of the study of the tourism capacity of Kelembak Village in Nongsa District resulted in a Physical Carrying Capacity/PCC value of 2630,76 visitors/day, and a Real Carrying Capacity/RCC of 149,95 tourists/day. The study shows that carrying capacity of Kelembak Village in Nongsa region tourists may reach the number of 2630,76 Physical Carrying Capacity/PCC visitors/day, and Real Carrying Capacity/RCC as much as 149,95 tourists/day. This shows that the current number of visits still does not exceed the real capacity of the Kelembak Village tourism object. The tourist location of Kelembak Village is still able and effective to accommodate the number of tourists allowed to enter without causing damage to the existing ecosystem